Zatrzymać czas - Jan Zieliński (Załącznik Kulturoznawczy)
An analysis of a poem Zegary w Trewirze (Clocks In Trier) by Stefan Napierski from his 1933 volume Obrazy z podróży (Travel Pictures). The interpretation includes on one hand the context of the only novel by Napierski, Rozmowy z cieniem (Conversations With A Shadow), in which the clocks play an important role, on the other hand the iconographical tradition of the time measuring in Trier, based mostly on the monography of that subject by Christl Lehnert-Leven (Uhren in Trier. Geschichte, Gedichte und Bestände des Museums Simeonstift 14 S. Napierski, Z powodu „Diogenesa w kontuszu” Wacława Berenta, „Ateneum” 1938, nr 2 s. 31.